Species distinctions among closely related strains of Eustigmatophyceae (Stramenopiles) emphasizing ITS2 sequence-structure data: Eustigmatos and Vischeria. Issue 4 (2nd October 2018) - Kryvenda, Anastasiia; Rybalka, Nataliya; Wolf, Matthias; Friedl, Thomas
ABSTRACT: There is an increasing interest in the Eustigmatophyceae, a class of stramenopile microalgae, because they offer a variety of high-value health-beneficial compounds, e.g. polyunsaturated fatty acids (PUFAs), while concomitantly producing high biomass. Clarification of the taxonomy of these organisms at the species level is important in order to achieve reproducible results and constant yields of valuable compounds in their exploitation. Here the distinction of the, so far exclusively, morphologically defined species of the genera Eustigmatos and Vischeria was tested. Distinctions inferred from almost full 18S and ITS2 rRNA as well as plastid-encoded rbc L gene sequences were evaluated following a morphological investigation. The ITS2 secondary-structure-based phylogenies separated independent lineages (species) with long internal branches. This recommends ITS2 as a promising marker for a DNA metabarcoding approach (culture-independent biodiversity assessment). In contrast, the 18S V4 region which is commonly used in metabarcoding was almost invariant, whereas the almost full length sequences distinguished eight groups/types of strains. Monophyly of the species was supported by shared ITS2 secondary structure features, making them distinct from other eustigmatophyte lineages in concordance with phylogenetic analyses. No groups of strains were congruently supported by all three markers. Consequently, the previous distinction of two genera on the basis of morphology cannot be retained and the species should be accommodated in a single genus, Vischeria . Taxonomic changes among the species with the definition of epitypes, on the basis of cryopreserved strains, are recommended. Two findings point to a more complex evolutionary history of the species. The rbc L and nuclear markers resulted in disparate groupings of strains. In three species divergent intragenomic ITS2 paralogues were revealed. Therefore, a still broader taxon sampling, in conjunction with a deep sequencing approach, is needed for a more comprehensive understanding of the complex evolution of eustigmatophyte species.